Limiting factors of investment activity of the sports industry on the example of international football competitions in Russia - Dougblay, A. D.; Lubyshev, E. A.; Titovsky, A. V.; Krasilnikov, A. A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the limiting factors of investment activity in the organization and holding of international football competitions in Russia.